Effects of process parameters variations and optimization of biodiesel production from waste cooking soya oil - Ugwu Hyginus Ubabuike; Ezere Yagazie Prosper; Igri O. Uket; Okon Jimmy Omini; Jacob Ukeme; Luke Uduak (International Journal of Engineering and Technology, 2024)
Waste cooking soya oil (WCSO) in this study was transesterified with methanol in the presence of sodium hydroxide (NaOH) as catalyst. The effects of the process parameters (catalyst concentration, reaction time, reaction temperature, methanol/sample ratio and agitation speed) were studied individually and in matrix form to establish synergistic interactions. Process optimal conditions that gave the maximum bio-diesel yield of 94.70 % were: catalyst concentration (1 %), reaction time (60 minutes), reaction temperature (70 oC), methanol/sample ratio (6:1), and agitation speed (300 rpm), while those that caused the lowest yield of 66.20% were catalyst concentration of 0.25 % at reaction time of 30 minutes, under the reaction temperature of 50 oC with methanol to sample ratio of 2:1, and agitation speed of 150 rpm. The phys-iochemical properties of the yield investigated revealed that the developed biodiesel properties conformed within the American Society for Testing and Materials (ASTM) and European (EN) standard recommendations. From the analysis, Cetane index of 74.12, kinematic vis-cosity of 4.43 mm2/s, density of 876.6 kg/m3, flash point of 142 oC, fire point of 150 oC, cloud point of 8.5 oC and moistuure content of 0.04 % were obtained for the biodiesel. Overall, the findings demonstrated that the technique employed if harnessed and commercialized, is a safe clean energy technology which utilizes waste materials that would have been harmful to the environment for the enhancement of hu-man and environmental wellbeing.